Multifunctional Graphdiyne Enables Efficient Perovskite Solar Cells via Anti-Solvent Additive Engineering - Shao, Cong; He, Jingyi; Ma, Jiaxin; Wang, Yirong; Niu, Guosheng; Zhang, Pengfei; Yang, Kaiyi; Zhao, Yao; Wang, Fuyi; Li, Yongjun; Wang, Jizheng (Nano-Micro Letters, 2025)
Finding ways to produce dense and smooth perovskite films with negligible defects is vital for achieving high-efficiency perovskite solar cells (PSCs). Herein, we aim to enhance the quality of the perovskite films through the utilization of a multifunctional additive in the perovskite anti-solvent, a strategy referred to as anti-solvent additive engineering. Specifically, we introduce ortho-substituted-4′-(4,4″-di-tert-butyl-1,1′:3′,1″-terphenyl)-graphdiyne (o-TB-GDY) as an AAE additive, characterized by its sp/sp2-cohybridized and highly π-conjugated structure, into the anti-solvent. o-TB-GDY not only significantly passivates undercoordinated lead defects (through potent coordination originating from specific high π–electron conjugation), but also serves as nucleation seeds to effectively enhance the nucleation and growth of perovskite crystals. This markedly reduces defects and non-radiative recombination, thereby increasing the power conversion efficiency (PCE) to 25.62% (certified as 25.01%). Meanwhile, the PSCs exhibit largely enhanced stability, maintaining 92.6% of their initial PCEs after 500 h continuous 1-sun illumination at 23 °C in a nitrogen-filled glove box. Highlights: 1 The use of novel nanographdiyne (o-TB-GDY) via anti-solvent additive engineering significantly enhances the nucleation and growth of perovskite crystals, leading to improved film quality, reduced film defects and suppressed non-radiative recombination. 2 o-TB-GDY primarily remains on the surface of the perovskite films after crystallization, where it strongly interacts with the undercoordinated Pb defects for effective passivation. 3 The optimized perovskite solar cells achieve a champion power conversion efficiency of 25.62% (certified as 25.01%) with good stability.